1999
DOI: 10.1136/bmj.319.7213.824
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of near patient test evaluations in primary care

Abstract: Objective To identify and qualitatively synthesise the findings from all studies that have examined the performance and effect of near patient tests in the primary care setting. Design Systematic review of published and unpublished research 1986-99. Main outcome measures Test performance characteristics, measures of effect on clinical practice or patient outcome. Results 101 relevant publications were identified. The general quality of these papers was low, and consequently only 32 papers were assessed in deta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 42 publications
0
28
1
Order By: Relevance
“…16,17 Participants' concerns reiterated observations made by Delaney et al, 18 who observed that without evidence to support the cost effectiveness of POCT, the implementation of this technology in primary health care settings would be low. A review by Baer 19 of the cost of POCT versus performing the same tests in laboratories found that approximately half of the studies reported POCT as being less expensive.…”
Section: Discussionmentioning
confidence: 97%
“…16,17 Participants' concerns reiterated observations made by Delaney et al, 18 who observed that without evidence to support the cost effectiveness of POCT, the implementation of this technology in primary health care settings would be low. A review by Baer 19 of the cost of POCT versus performing the same tests in laboratories found that approximately half of the studies reported POCT as being less expensive.…”
Section: Discussionmentioning
confidence: 97%
“…48,68,71 While local PoCT models have been developed for use in the Australian rural general practice environment 47 , the evidence base for the usefulness of PoCT in general practice both within Australia and globally has thus far been limited. 3,13 The objectives of this component of the PoCT Trial in General Practice were to develop, deliver and manage both:…”
Section: Discussionmentioning
confidence: 99%
“…13 To date, there has been no research investigating whether PoCT improves patient compliance with disease management, particularly in terms of effect on the use of medicines, diet and exercise compared to usual care (pathology laboratory testing). Research by Shephard et al 68 investigating whether PoCT was an effective intervention in improving clinical outcomes for Aboriginal patients with diabetes did not investigate patient compliance to medication but showed that 93% of patients felt that regular PoCT encouraged them to look after their health better.…”
mentioning
confidence: 99%
“…10 A systematic review of near-patient testing in primary care, published in 1999, concluded that there was little research evidence to guide expansion of the use of near-patient testing, and further research was recommended. 11 Ten years on, there has been little progress in terms of rigorous evaluations of near-patient testing initiatives in primary care. A recent guideline summarised some of the evidence base for near-patient testing, especially in emergency departments, but the evidence base for its impact in…”
Section: Tailoring Treatment To Risk In Type 2 Diabetesmentioning
confidence: 99%